Grupos de interesses e as práticas de gestão na escola pública básica: um estudo de multicasos - Singh, Ananda Silva (2016)
Public education can be considered an aspect of great relevance nationally speaking, since great amounts of investment has been dedicated to it in the past years. Once the school is seen as one of the main ways the majority of the population have to gain knowledge, it is of great importance that studies that talk about school management take place in the academic literature, since that the later consists of a way to achieve principles, guidelines and educational goals that guide the promotion of educational actions with social quality. However, it is common in school management, the unique presence of the principal as the main commandant of all members and of other stakeholders of the school. Thus, it is possible to realize that the existence of managerial practices aimed towards the needs of stakeholders of the school, other than its managers’ needs, is minimum or even absent. In this context, this research aims to bring the principles of the Stakeholder Theory to public schools’ management, analyzing how managerial practices of public basic schools take place, in the city of Uberlândia, when it comes to its relations with the school’s stakeholders. In order to do so, this research consisted of a qualitative analysis, using three sources of data: documents from the school, direct observations and semi-structured interviews. After being collected, the data were analyzed through the “content analysis” technique. In this stage of the research, the data collected were presented and analyzed based on categories defined before and after the data collection, related to the components of the managerial methods proposed by Chanlat (1996) and to Freeman and McVea’s (2000) Stakeholder Theory. Some of the results found in this research were: identification of the main stakeholders of the schools, the presence of conflicting goals between the schools and its stakeholders, the values that act as key-elements of managerial practices and processes, the influence and the degree of involvement and participation of the school’s stakeholders in each component of the managerial method proposed by Chanlat (1996). The main limitations of this research are: the amount of schools that were studied doesn’t allow generalization of results, the type of schools that were studied (municipal school) doesn’t allow knowing the scenario of other types of schools (state schools, for example) and the lack of documents – especially in school B – regarding some aspects of two of the analyzed categories made it difficult to fully analyze them.